2009
DOI: 10.1142/s179304800900106x
|View full text |Cite
|
Sign up to set email alerts
|

Life and Gravity

Abstract: All organisms on earth have evolved at unit gravity and thus are probably adapted to function optimally at 1 g. However, with the advent of space exploration, it has been shown that organisms are capable of surviving at much less than 1 g, as well as at greater than 1 g. Organisms subjected to increased g levels exhibit alterations in physiological processes that compensate for novel environmental stresses, such as increased weight and density-driven sedimentation. Weight drives many chemical, biological, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 101 publications
(96 reference statements)
0
4
0
Order By: Relevance
“…Among them, centrifuge systems have been widely used to analyze the effect of hypergravity perception and response in plants. Exposures to hypergravity values have been shown to affect growth, development and cell wall properties in various plants (Waldron and Brett 1990;Hoson et al 1996;Soga et al 1999a, b;Tamaoki et al 2006;Nakabayashi et al 2006;Bhaskaran et al 2009). In most of the earlier reports, three to five days old seedlings were exposed to higher g values up to 300 g for longer durations and effects were studied.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, centrifuge systems have been widely used to analyze the effect of hypergravity perception and response in plants. Exposures to hypergravity values have been shown to affect growth, development and cell wall properties in various plants (Waldron and Brett 1990;Hoson et al 1996;Soga et al 1999a, b;Tamaoki et al 2006;Nakabayashi et al 2006;Bhaskaran et al 2009). In most of the earlier reports, three to five days old seedlings were exposed to higher g values up to 300 g for longer durations and effects were studied.…”
Section: Introductionmentioning
confidence: 99%
“…Besides a pure vectorial addition or subtraction some species can even actively accelerate during upward swimming and decelerate during downward swimming, thereby at least partially compensate passive sedimentation (Häder et al 2005a), a phenomenon which is called gravikinesis (Machemer et al 1991;Machemer and Machemer-Röhnisch 1996;Gebauer et al 1999;Bhaskaran et al 2009) and is found in many ciliates such as Paramecium, Loxodes, Didinium and Stylonychia (Krause et al 2010) and is controversially discussed in Euglena (Machemer-Röhnisch et al 1999;Häder et al 2005a). …”
Section: Introductionmentioning
confidence: 99%
“…Thus, life forms are not only shaped by this important physical force but adapted to use it for their own benefit (Morey-Holton, 2003;Bhaskaran et al 2009). Plants respond to gravity in different levels that range since intracellular mechanisms until growth and development, in a way that arranges their spatial orientation and survival (Bhaskaran et al 2009). In this study, we show that gravity influences flower resupination in two different but complementary ways: gravitropism and gravitation.…”
Section: Discussionmentioning
confidence: 63%
“…The direction and intensity of gravity have been constant throughout the evolutionary history of life on Earth, acting on all organisms. Thus, life forms are not only shaped by this important physical force but adapted to use it for their own benefit (Morey-Holton, 2003;Bhaskaran et al 2009). Plants respond to gravity in different levels that range since intracellular mechanisms until growth and development, in a way that arranges their spatial orientation and survival (Bhaskaran et al 2009).…”
Section: Discussionmentioning
confidence: 99%